2016
DOI: 10.3892/mmr.2016.5273
|View full text |Cite
|
Sign up to set email alerts
|

PRMT1 regulates tumor growth and metastasis of human melanoma via targeting ALCAM

Abstract: Hepatocellular carcinoma (HCC) is a major type of liver cancer caused by the hepatitis B and C viruses, alcohol and exposure to aflatoxin. For HCC treatment, anticancer drugs have been widely used, but drug resistance in advanced HCC is an important problem, resulting in a continuous need for novel therapeutic targets. Therefore, in this study, we established a screening pipeline based on RNA-seq to screen novel therapeutic/prognostic targets in HCC and identified PRMT1 (Protein Arginine Methyltransferase 1). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
(29 reference statements)
2
11
0
Order By: Relevance
“…Finally, cryptotanshinone, a STAT3 inhibitor, suppressed HCC growth and migration through inhibiting STAT3 phosphorylation, which was activated by PRMT1 overexpression. Previous studies indicated that PRMT1 overexpression led to the progression and metastasis of various cancers and predicted a worse prognosis in patients [10,12,13]. Furthermore, Nakai, et al reported that EGFR methylation and activity were significantly reduced in PRMT1 knockdown cells compared to the triple-negative breast cancer parental cells [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, cryptotanshinone, a STAT3 inhibitor, suppressed HCC growth and migration through inhibiting STAT3 phosphorylation, which was activated by PRMT1 overexpression. Previous studies indicated that PRMT1 overexpression led to the progression and metastasis of various cancers and predicted a worse prognosis in patients [10,12,13]. Furthermore, Nakai, et al reported that EGFR methylation and activity were significantly reduced in PRMT1 knockdown cells compared to the triple-negative breast cancer parental cells [9].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, due to the close relationship between protein arginine methylation and various types of tumours, an increasing number of researchers have begun to study the relationship between PRMTs and cancer, especially PRMT1. PRMT1 regulates tumour growth and metastasis in human melanoma via targeting ALCAM [10]. In triple-negative breast cancer, PRMT1 is critical for epidermal growth factor receptor (EGFR) activity, and inhibiting PRMT1 may be an effective therapeutic strategy for overcoming intrinsic cetuximab resistance in triplenegative breast cancer cells [11].…”
Section: Introductionmentioning
confidence: 99%
“…An estimated 1,361,000 people are diagnosed with CRC every year; approximately 694,000 people die from CRC annually; and 3,544,000 individuals are living with Recent studies have linked this modification to carcinogenesis and metastasis. Alterations to the PRMTs sequences have not been found so far; however, over expression of these enzymes is very often associated with the progression of various cancers [6,7]. Among PRMT family proteins, PRMT1 is crucial for the majority (approximately 85%) of methylated arginine in mammalian cells [4].…”
Section: Introductionmentioning
confidence: 99%
“…Although it has taken 50 years to acknowledge the significance of PRMTs in cancer, the pace at which major discoveries have been made in recent years is phenomenal. Disruption of ADMA modification at key substrates decreases the metastatic and proliferative ability of cancer cells (Li et al, 2016), suggesting that PRMT inhibitors may be an effective strategy to combat different types of cancer. Several PRMT inhibitors have entered or are on the verge of entering the clinic, but how they alter global protein ArgMet levels remains to be uncovered.…”
Section: Nmr Reveals Modulation and Dynamics Of Protein Argmetmentioning
confidence: 99%